Improving Descriptive Text Writing Achievement through the Demonstration Method among Seventh Grade Students - Habibi Afnianda (PT. Mifandi Mandiri Digital, 2023)
This study is a Classroom Action Research (CAR) aimed at improving students' learning outcomes in writing descriptive texts through the use of the demonstration method. The research subjects were 21 seventh-grade students of MTs Alwashliyah Pantai Labu. The study was conducted in two cycles, each consisting of one meeting. Data collection techniques included learning outcome tests administered at the end of each cycle and a questionnaire distributed during the second cycle. The research design followed the Kurt Lewin model, which involves planning, action, observation, and reflection. Data analysis was carried out using descriptive statistics by calculating the class average and the percentage of mastery learning, with a minimum completeness criterion of 80%. The findings indicate that the implementation of the demonstration method significantly enhanced both the learning process and the students' achievement in writing descriptive texts. Therefore, the demonstration method is considered effective for teaching descriptive text writing to seventh-grade students at MTs Alwashliyah Pantai Labu.